Pesan Iklan Shopee Al dan Andin sebagai Strategi Komunikasi Pemasaran - Nur Aolia, Fira Pramudita; Muhtadi, Asep Saeful; Dulwahab, Encep (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2021)
This study aims to find out how Shopee's marketing communication strategy is through content analysis of messages in Shopee advertisements for the Al and Andin period. This study uses the concept of message strategy and media strategy promoted by Mahmud Machfoedz. This study uses a qualitative analysis method with primary and secondary data through data collection techniques, namely observation, and documentation. The results of the study resulted in several conclusions: first, a rational idea of information regarding market needs, benefits, and advantages, as well as an invitation to use Shopee; emotional ideas include feelings of pleasure, worry, panic, competitiveness, and curiosity as triggers so that people want to do what the company wants; and moral ideas include the 'Big Ramadan Sale and #ShopeeAdaUntukUMKM campaigns; second, Shopee conveys these advertising ideas using online media, television and the game features of the Shopee platform. The above strategy is supported by the use of time and consumer behavior as a consumer gap.